KEMANDIRIAN INSTRUMENTAL ACTIVITY DAILY LIVING (IADL) PENYINTAS SKIZOFRENIA PEKERJA JOB CLUB - Nisa, Aziizah Khairun; Pangestuti, Retno (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2025)
ABSTRAK Independence in daily activities is very important for schizophrenia survivors, but disturbances in this aspect have the potential to cause serious problems such as impaired role function, decreased productivity, and increased dependency that burdens families and society. This study aims to determine the description of instrumental independence in daily living activities among job club workers at Klender Islamic Mental Hospital. This study used a qualitative phenomenological method with three informants, two men and one woman, with the following characteristics: schizophrenia survivors who had previously undergone rehabilitation at Klender Islamic Mental Hospital, participated in the Job Club program, and were aged 35-44 years. This study found that schizophrenia survivors participating in the Job Club program at the Klender Islamic Mental Hospital demonstrated varying levels of independence in performing instrumental activities of daily living (IADLs) such as shopping, cooking, cleaning, managing finances, and using transportation. Two out of three informants were able to perform these activities independently, while one informant still required assistance. This level of independence is influenced by participation in Job Clubs as well as other factors such as cognitive development, parenting styles, and socioeconomic environment. These findings suggest that with structured support and ongoing rehabilitation, schizophrenia survivors can rebuild functional independence and return to their roles in society. Kemandirian dalam aktivitas sehari-hari sangat penting bagi penyintas skizofrenia, namun gangguan pada aspek ini berpotensi menimbulkan masalah serius seperti terhambatnya fungsi peran, menurunnya produktivitas, serta meningkatnya ketergantungan yang membebani keluarga dan masyarakat. Penelitian ini bertujuan untuk mengetahui gambaran kemandirian instrumental activity daily living pada pekerja job club RSJ Islam Klender. Penelitian ini menggunakan metode kualitatif fenomenologi dengan informan  berjumlah 3 orang, 2 laki-laki dan 1 perempuan, dengan ciri-ciri: penyintas skizofrenia yang sebelumnya pernah menjalani rehabilitasi di Rumah Sakit Jiwa Islam Klender, mengikuti program Job Club, dan berusia 35-44 tahun. Penelitian ini menemukan bahwa penyintas skizofrenia yang mengikuti program Job Club di RSJ Islam Klender menunjukkan tingkat kemandirian yang bervariasi dalam melakukan aktivitas instrumental kehidupan sehari-hari (IADL) seperti berbelanja, memasak, membersihkan rumah, mengelola keuangan, dan menggunakan transportasi. Dua dari tiga informan mampu menjalankan aktivitas secara mandiri, sedangkan satu informan masih memerlukan pendampingan. Tingkat kemandirian ini dipengaruhi oleh partisipasi dalam Job Club serta faktor-faktor lain seperti perkembangan kognitif, pola asuh, dan lingkungan sosial ekonomi. Temuan ini menunjukkan bahwa dengan dukungan yang terstruktur dan rehabilitasi yang berkelanjutan, penyintas skizofrenia dapat membangun kembali kemandirian fungsional dan berperan kembali di masyarakat.